2018
DOI: 10.1038/s41582-018-0013-z
|View full text |Cite
|
Sign up to set email alerts
|

Tau-targeting therapies for Alzheimer disease

Abstract: Alzheimer disease (AD) is the most common form of dementia. Pathologically, AD is characterized by amyloid plaques and neurofibrillary tangles in the brain, with associated loss of synapses and neurons, resulting in cognitive deficits and eventually dementia. Amyloid-β (Aβ) peptide and tau protein are the primary components of the plaques and tangles, respectively. In the decades since Aβ and tau were identified, development of therapies for AD has primarily focused on Aβ, but tau has received more attention i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
727
1
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 882 publications
(750 citation statements)
references
References 222 publications
(254 reference statements)
11
727
1
11
Order By: Relevance
“…Therefore, seeking therapeutic alternatives for AD that target tau proteins has recently captured researchers’ interest. In this context, there are many ongoing investigations targeting the accumulation of tau proteins, among others, is the immunotherapy approach that indicated promising results reported about the clinical trials progress of many antibodies and vaccines for the potential treatment of AD …”
Section: Future Directions For Alzheimer's Disease Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, seeking therapeutic alternatives for AD that target tau proteins has recently captured researchers’ interest. In this context, there are many ongoing investigations targeting the accumulation of tau proteins, among others, is the immunotherapy approach that indicated promising results reported about the clinical trials progress of many antibodies and vaccines for the potential treatment of AD …”
Section: Future Directions For Alzheimer's Disease Treatmentmentioning
confidence: 99%
“…In this context, there are many ongoing investigations targeting the accumulation of tau proteins, among others, is the immunotherapy approach that indicated promising results reported about the clinical trials progress of many antibodies and vaccines for the potential treatment of AD. 184,185 In addition, numerous preclinical studies were performed to reduce tau production by targeting tau gene expression via the antisense oligonucleotide-based approach. The latter is currently in phase I clinical trials.…”
Section: Cannabinoid Type 2 Receptor Agonistsmentioning
confidence: 99%
“…In later studies, we showed that tau antibodies could have the same effect [5,6], and provided various insights into the possible mechanisms of clearance [7–19]. These studies have been confirmed and extended by various groups showing benefits of immune-targeting the pS396/404 tau epitope [2,4,69,12,2027], and other tau epitopes [20,2325,2749], which as mentioned above has resulted in eight clinical trials (for a recent review of these trials see [50]), with several more likely to be initiated in the near future. We have highlighted many of these studies in some details in various reviews over the years as they have been reported so it is not necessary to elaborate further on those particular aspects (see for example [5153]).…”
Section: Introductionmentioning
confidence: 83%
“…Intracellular aggregates of the tau protein, with the properties of amyloid fibrils, are the defining feature of a group of neurological disorders known as tauopathies, which include Alzheimer's disease (AD) . Tau pathology has been recognized as a target for the development of disease‐modifying therapies, the success of which requires to acquire a deep knowledge on the multiple molecular factors that contribute to the formation of neurotoxic aggregates …”
Section: Figurementioning
confidence: 99%